2022
DOI: 10.3390/jcm11247296
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease Patients’ Acceptance for Switching from Intravenous Infliximab or Vedolizumab to Subcutaneous Formulation: The Nancy Experience

Abstract: Background: Subcutaneous infliximab and vedolizumab formulations have been developed for maintenance therapy in inflammatory bowel disease. The objective of this study was to explore the inflammatory bowel disease patient’s acceptance for switching from intravenous infliximab or vedolizumab to subcutaneous, as well as to describe the causes of refusal or, conversely, the factors associated with acceptance. Methods: Patients were prospectively recruited between June 2021 and March 2022 during their infusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…Other influential factors included a fear of needles, the belief that infusion is more effective, extended intervals between infusions, and a desire for consultations with a doctor after each treatment. This aligns with findings from a previous study in France, where patients resisted switching from IV to SC due to concerns about a potential loss of efficacy, a more spaced-out medical follow-up, increased administration frequency, and the introduction of self-administered injections [15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Other influential factors included a fear of needles, the belief that infusion is more effective, extended intervals between infusions, and a desire for consultations with a doctor after each treatment. This aligns with findings from a previous study in France, where patients resisted switching from IV to SC due to concerns about a potential loss of efficacy, a more spaced-out medical follow-up, increased administration frequency, and the introduction of self-administered injections [15].…”
Section: Discussionsupporting
confidence: 88%
“…Notably, only a quarter of patients were aware of the subcutaneous administration option for therapeutic agents [ 14 ]. In a study conducted at Nancy Hospital in France, 16.7% of vedolizumab patients and 24.5% of those treated with infliximab declined to transition from IV to SC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some patients, moreover, dislike the idea of self-injecting or more frequent dosing of subcutaneous formulations [ 15 ]. In recent studies on patient acceptance of switching from intravenous infliximab or vedolizumab to subcutaneous formulations of the drug, the majority (58–78%) of the patients accepted the switch, and the main motivation was saving time [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…51 A relatively large number of trials on VDZ SC reported satisfactory outcomes. 34,[36][37][38][39][40][41][52][53][54][55][56][57][58][59][60] Therefore, we sought to systematically review studies on VDZ SC for treating patients with IBD and to meta-analyze studies with relatively complete outcomes.…”
Section: Discussionmentioning
confidence: 99%